Childcare Centre Facilities and their Impact on the Performance of Working Mothers in Dhaka, Bangladesh - Nahida Shaulin (Journal of Asian Social Science Research, 2024)
In Bangladesh, it is common for working women to experience increased concerns about the safety and well-being of their children after childbirth. This study aims to examine the impact of childcare facilities on the occupational productivity of employed women in Bangladesh, specifically within Dhaka City. A quantitative research approach was utilized, with statistical analyses including frequency distribution, descriptive statistics, reliability analysis, and a chi-square test. The results of the chi-square test (p<0.05) demonstrated a significant relationship between the availability of childcare center facilities and the job performance of working mothers. The study found that most participants believed that reliable childcare facilities positively influenced their work-life balance. These findings offer valuable insights for policymakers, highlighting the need for more reliable childcare facilities in Dhaka City to enhance the active participation of working mothers in the workforce and their ability to deliver high-quality performance. While the past decade has seen considerable research on women's empowerment and increasing female representation in the labor market, this study is the first to specifically address the impact of childcare center facilities on the workplace performance of working mothers.